2018
DOI: 10.1111/dmcn.13689
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of developmental screening in young children with sickle cell disease: a longitudinal follow‐up study

Abstract: Developmental screening predicts academic outcomes in sickle cell disease. Children with concerning language/cognitive screenings have early-onset school difficulties. Developmental screenings may help predict cerebrovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…This may be an artificial effect related to small numbers since most of our patients were non‐Hispanic Black or Hispanic, or it could suggest a vulnerability in our school system. Disease type and risk level based on health care claims were associated with some differences in chronic absenteeism but no differences were seen in the school attendance analysis which is surprising; we had expected higher health care utilization indicated worse disease control and/or worse disease severity, and that would be associated with poorer school attendance 28‐33 …”
Section: Discussionmentioning
confidence: 88%
“…This may be an artificial effect related to small numbers since most of our patients were non‐Hispanic Black or Hispanic, or it could suggest a vulnerability in our school system. Disease type and risk level based on health care claims were associated with some differences in chronic absenteeism but no differences were seen in the school attendance analysis which is surprising; we had expected higher health care utilization indicated worse disease control and/or worse disease severity, and that would be associated with poorer school attendance 28‐33 …”
Section: Discussionmentioning
confidence: 88%
“…12 However, as Schatz et al showed, developmental screening in both toddler-aged and school-aged children can predict later poor academic achievement and grade retention. 13 Prior to now, the only screening for poor academic performance (PAP) at our institution's sickle cell clinic was to ask for parental concerns regarding their child's school performance and whether an IEP/504 was in place.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these same children had elevated risks for abnormal TCD and stroke on magnetic resonance imaging. 3 Schatz et al's study demonstrates the value in completing developmental and cognitive screening in this high-risk population. Screening results may be helpful in implementing a more thorough imaging screening program and more aggressive referral program for early intervention services like speech, occupational and physical therapy, and academic support.…”
mentioning
confidence: 99%
“…Deficits are present at a young age; developmental delay has been documented in 25% to 50% of clinic populations of preschool-aged children with SCD. 2,3 Those affected are usually African American and living at or near the poverty level. These factors are major obstacles for the children as they enter an academic setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation